Meningkatkan Minat Belajar Peserta Didik Melalui Model Pembelajaran Project Based Learning Pada Kelas II SDN 50 Cakranegara - Nurfitryana, Nurfitryana; Arjudin, Arjudin; Kaninta, Novianti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Purpose of this Study is to increase students' interest in learning in thematic learning through the project based learning (PjBL) model for class II SDN 50 cakranegara for the 2022/2023 academic year, with a total of 29 students. This type of research is collaborative classroom action research. The instrument used in this study was an observation sheet of students' learning interest through the project based learning (PjBL) model . The results showed that the learning interest of students in thematic learning increased as indicated by the average score obtained in cycle I, namely 3.13 in the medium category and the average score obtained in cycle II, namely 4.25 in the high category. Based on the results of this study, it can be concluded that the project based learning (PjBL) learning model can increase students' learning interest in class II thematic learning at SDN 50 Cakranegara.